Cyclometalated Ruthenium(II) NHC Complexes with Imidazo[1, 5‐a]pyridine‐Based (C^C*) Ligands – Synthesis and Characterization. Issue 14 (25th February 2019) - Schleicher, David; Tronnier, Alexander; Soellner, Johannes; Strassner, Thomas
Abstract : We present the synthesis and characterization of cyclometalated ruthenium(II) NHC complexes with phenyl‐substituted imidazo[1, 5‐ a ]pyridine C ^ C* ligands. The corresponding p ‐cymene complexes can be reacted with bipyridine to form bisheteroleptic ruthenium(II) dyes. The compounds have been characterized by one‐ and two‐dimensional 1 H/ 13 C NMR spectroscopy, elemental analysis, cyclic voltammetry, infrared spectroscopy, as well as solid‐state structure (X‐ray) analysis. Abstract : Ruthenium complexes bearing cyclometalated N‐heterocyclic carbene based on an imidazo[1, 5‐ a ]pyridine motif are synthesized and fully characterized via NMR, UV/Vis, CV, and X‐ray techniques.